Determinants of Pediatric Tuberculosis Patient Recovery in Semarang City - Tristanti, Wita Istiqomah; Fauzi, Lukman (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: Tuberculosis is an infectious disease which is the main cause of death worldwide caused by the bacterium Mycobacterium tuberculosis. This bacterium can infect children to adults. According to data from the Semarang City Health Office for 2022, Semarang City is one of the regions in Indonesia that has played a role in realizing national tuberculosis cases with a cure rate that is still far from the global target, namely 78,95% in 2020 and 71,72% in in 2021. The purpose of this study was to determine the factors that can affect recovery in pediatric tuberculosis patients in Semarang City.Methods: The type of research used was analytic observational with a retrospective cohort study design. This study used secondary data from the SEMAR BETUL system from January 2021-September 2022.Results: The results showed that ownership of the supervisor swallowed the drug (PMO) (p<0.001; AOR= 13.997, 95% CI= 8.728-22.446) and house humidity variable (p= 0.002; AOR= 2.059. 95% CI= 1.290-3.287) effect on the recovery of pediatric tuberculosis patients in the city of Semarang.Conclusion: It is known that the supervisor ownership variable for ingesting drugs is the strongest factor influencing the recovery of pediatric tuberculosis patients in Semarang City.